2018
DOI: 10.1002/tie.21986
|View full text |Cite
|
Sign up to set email alerts
|

Expatriates' identity salience, work stressors, and work–nonwork conflict: Moderating role of gender and marital status

Abstract: Drawing from identity theory, we proposed individuals with high work salience experienced high work stressors (interpersonal conflict, workhours, and workload), resulting in positive worknonwork conflict (WNWC), and individuals with high nonwork salience experienced lower work stressors, resulting in negative WNWC. Furthermore, we tested for the moderating role of gender and marital status in the relationship. The sample for this study consisted of 415 Indian expatriates working in the U.S. information technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In this context, the attitudes and behaviors toward the new culture that immigrants have entered are a matter that should be considered in terms of their own living standards and adaptation to the new culture. But, research on foreign residents or expats have generally focused on marital status, job performance, age, length of stay, education, and status, considering the intercultural adaptation and adaptation process (Groves & O'Connor, 2018;Haak Saheem et al, 2019;Hincks, 2018;Nunes et al, 2017;Takeuchi et al, 2019;Vijayakumar & Cunninham, 2019). Therefore, this study, unlike previous studies, has been able to fill a gap in the literature by examining the eating behaviors of foreign residents in general, and specifically understanding the attitudes toward Turkish cuisine in particular.…”
Section: Conceptual Contributionmentioning
confidence: 99%
“…In this context, the attitudes and behaviors toward the new culture that immigrants have entered are a matter that should be considered in terms of their own living standards and adaptation to the new culture. But, research on foreign residents or expats have generally focused on marital status, job performance, age, length of stay, education, and status, considering the intercultural adaptation and adaptation process (Groves & O'Connor, 2018;Haak Saheem et al, 2019;Hincks, 2018;Nunes et al, 2017;Takeuchi et al, 2019;Vijayakumar & Cunninham, 2019). Therefore, this study, unlike previous studies, has been able to fill a gap in the literature by examining the eating behaviors of foreign residents in general, and specifically understanding the attitudes toward Turkish cuisine in particular.…”
Section: Conceptual Contributionmentioning
confidence: 99%
“…For example, Truman et al (2011) reported that expatriate workers experienced a 50% higher risk for mental health problems, such as internalizing problems (stress, suicide, anxiety, loneliness, and depression), externalizing problems (attention deficit, hyperactivity, conduct and impulse control), and substance misuse disorders, compared to native workers. Expatriate workers may also experience challenges with cognition such as difficulties with understanding relationships, misunderstandings caused by cultural differences, frustration, insomnia, fear of isolation, the uncertainty of the future, concerns over health and security, and decreased well-being (Chen 2019;Doki et al 2018;Gai et al 2011;Vijayakumar and Cunningham 2019). Ward and colleagues (2001) reported that successful cross-cultural adjustment is the culmination of enhanced emotional resilience, effective cognitive restructuring, and the display of appropriate behavioral and social skills.…”
Section: Psychological Adjustmentmentioning
confidence: 99%
“…In the above discussion, we find that there are different views to explain the gender gap in employment hours. However, there is little discussion about the effects of marital status to the gender gap taking marital status as moderator, although there are some of the studies (e.g., (Boeckmann, Misra, & Budig, 2014;Janse van Rensburg, Claassen, & Fourie, 2019;Olivetti, 2006;Tumsarp & Pholphirul, 2020;Vijayakumar & Cunningham, 2019)) that focused on marital status. But these studies do not show the interaction between marital status, gender gap and employment hours.…”
Section: Introductionmentioning
confidence: 99%